Early active mobilization after pediatric extensor tendon repair: a case report - Kaur, Ramandeep (International Surgery Journal, 2025)
Extensor tendon injuries in children are relatively uncommon but require precise repair and a well-monitored rehabilitation protocol for optimal outcomes. Early mobilization is considered beneficial in selected cases to prevent adhesions and stiffness. We report a case of a 6-year-old girl, left-hand dominant, who presented with a glass-cut injury over the dorsum of the left hand. Examination revealed a complete laceration of extensor tendons at Zone V. Surgical repair was performed using a modified Kessler core suture technique with an epitendinous running suture for reinforcement. Postoperatively, early mobilization was initiated on Day 3 using a dorsal protective splint, combined with controlled active extension and passive flexion exercises under supervision. The child showed excellent compliance and progressive improvement in range of motion. By 8 weeks, full active extension and flexion were achieved, with no extensor lag or stiffness. Functional outcome was satisfactory, and the child resumed full activity. Early mobilization following extensor tendon repair using a child-adapted rehabilitation protocol can lead to excellent functional outcomes, even in pediatric patients. Strict splinting, guided therapy, and family involvement are key.